Renormalisation group invariants and sum rules: fast diagnostic tools for probing high-scale physics - Hetzel, Jamil; Beenakker, Wim (Journal of high energy physics, 2012)
A method is described to probe high-scale physics in lower-energy experiments by employing sum rules in terms of renormalisation group invariants. The method is worked out in detail for the study of supersymmetry-breaking mechanisms in the context of the Minimal Supersymmetric Standard Model. To this end sum rules are constructed that test either specific models of supersymmetry breaking or general properties of the physics that underlies supersymmetry breaking, such as unifications and flavour-universality.